Strategic changes adopted by Saudi National Center for Crisis and Health Disaster Management after Pandemic Covid-19 - Al-Qudah, Hasan Salih; Al-Subahi, Nizar Abdulhai; Hobani, Mashael Ahmad (Journal of Economic, Administrative and Legal Sciences, 2023)
This current study sought to examine the strategic changes adopted by the Saudi National Health Emergency Operation Center (NHEOC) post COVID 19 and the Saudi approaches to manage health risks after the pandemic (Improving the quality and efficiency of health services, digitizing the health and increasing the coverage of services to all regions of the Kingdom). In other words, the study aimed at identifying changes in dealing with health risks within the Saudi Kingdom in accordance with the Kingdom vision 2030 specifically within health sector. The study adopted quantitative approach through distributing an online questionnaire on a random sample of (65) managers and officers within (NHEOC) in order to collect primary data. SPSS was used to tackle the primary data and results indicated the acceptance of all hypotheses, as it appeared that (NHEOC) adopted strategies that reconstructed the health sector in terms of improving the quality and efficiency of health services, digitizing the health and increasing the coverage of services to all regions of the Kingdom. The study has reached some highlighted recommendations like: Increasing effectiveness of the university's role with regarding to Kingdom's vision 2030 with regards to health crises and writings. By strengthening the partnership in developing education and health sector and developing this relationship through integration and achievements. Enhancing administrative awareness on the importance of quality health services based on the link between strategic objectives of National Center for Health Crisis and Disaster Management with the Kingdom's Vision 2030 especially in the field of health sectors and providers at all levels.* This research work was funded by the Institution Fund Projects under grant No. (IFPAS-84-849-1443). Therefore, the authors gratefully, acknowledge technical and financial support from the Ministry of Education and King Abdelaziz University, Jeddah, Saudi Arabia.
Keywords: National Center; Crisis Management; Covid 19; Health Sector; Quality; Efficiency; Digitization